Clinical, etiological and echocardiographic profile of atrial fibrillation in a tertiary care hospital: a cross-sectional observational study - Shashank Narayanappa; Shehla Ashraf; Purna Chand Paidi; Charunmayi Lakshmi Brahmani Adari; Raymond Haward (International Journal of Research in Medical Sciences, 2026)
Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia and is associated with increased morbidity, mortality, heart failure, thromboembolism, and reduced quality of life. The etiological spectrum of AF varies across populations, with rheumatic heart disease (RHD) remaining an important cause in developing countries. Echocardiography is essential for evaluating structural cardiac abnormalities in AF. Methods: A hospital-based cross-sectional observational study was conducted among 100 patients with AF admitted to a tertiary care teaching hospital. Clinical history, physical examination, electrocardiography, laboratory investigations, and transthoracic echocardiography were performed. Clinical characteristics, etiologies, echocardiographic findings, and complications were analyzed. Results: Most patients were elderly, with a female predominance. Dyspnea and palpitations were the most common presenting symptoms. RHD was the leading cause of AF, followed by hypertensive and ischemic heart disease. Mitral stenosis was the most frequent valvular lesion. Left atrial enlargement was the predominant echocardiographic finding, while varying degrees of left ventricular systolic dysfunction were also observed. Heart failure and stroke were the major complications. Valvular AF was more common than non-valvular AF. Conclusions: AF in this population was predominantly associated with rheumatic valvular heart disease and structural cardiac abnormalities, particularly left atrial enlargement. Early clinical and echocardiographic evaluation is essential for identifying underlying causes, stratifying risk, and preventing complications such as heart failure and thromboembolism.